On the separation of isolated solutions of nonlinear integral equations - Babich, M. D. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We present the theoretical justification and a method for practical realization of the process of separation of solutions isolated in a bounded domain for some classes of nonlinear integral equations. We study the problem of construction of a sequence of approximation equations by the method of mechanical quadratures and the problem of existence of solutions of these equations. We also present methods for approximate solution of these equations and obtaina posteriori error estimates.